Penerapan Pendekatan Student Centered Learning Dalam Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen Kelas V SD Inpres Naimata - Bait, Nurdiana; Luji, Daud Saleh (Institut Agama Kristen Negeri (IAKN) Ambon, 2023)
Abstract: Academic achievement is often the main goal of a learning activity. SCL is one of the approaches that helps students get a better learning performance. Thus the goal to be achieved in this study is to analyze and find out how affective the SCL method is on students’ academic achievements. The experiment was done with a quantitative approach. Data collection was done through tests namely pre-test and post-test. In this study, in order to reach the objectives, it was tested through prerequisite analysis and hypothesis exams. The result obtained were that the average score of the experimental class for the pre-test was 75.96 and 94.71 for the post-test, resulting in an increase of 18.75. which means it can be concluded there is a significant increase in students’ academic scores in the experimental class by applying the SCL approach to Christian Religion in Year 5 of Inpres Naimata Primary School. Keywords: Student Centered Learning Approach,Academic Achievement, PAK,